Industrial legislation in Australia in 2015. (June 2016) - Forsyth, Anthony
This review article examines the impact of another year of tumult in federal politics on the Coalition Government's workplace reform agenda. The article outlines the fortunes of the industrial relations bills the Government had introduced into Parliament in 2013–2014, and a number of others introduced in 2015. These include a bill to implement former Prime Minister Tony Abbott's proposed dilution of the federally-funded paid parental leave scheme. In addition, the Productivity Commission's proposals for changes to the federal workplace relations framework are examined and assessed, along with the Royal Commission into Trade Union Governance and Corruption Final Report, as these are shaping the reform debate in the lead-up to the forthcoming federal election. The article then examines significant legislative developments at state level. The article concludes by assessing the likely direction of labour law change under Prime Minister Malcolm Turnbull.